Two-component polyurethane structural adhesive and its application
Through the design of thermally conductive two-component polyurethane structural adhesive, the use of specific ratios and catalysts, the problems of insufficient curing speed and moisture interference of polyurethane adhesives in the prior art are solved, and long operating time and rapid thermal curing are achieved, which is suitable for complex battery electricity Adhesion and fixation of core components.
Patent Information
- Application Number
- CN202211575059.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-08
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-12-08
AI Technical Summary
The existing two-component polyurethane adhesives are insufficient in curing speed under short-term heating conditions, and there are foaming problems caused by moisture interference, which affects adhesion and insulation performance, making it difficult to be suitable for the electronic components industry that strictly eliminates moisture.
Component A is prepared by using thermally conductive two-component polyurethane structural glue with specific ratios of bisphenol A modified polyether polyol, castor oil modified polyol, heat activation catalyst, inorganic filler, thixotropic agent and water removal agent , and the B component made of terminal isocyanate-based polyurethane prepolymer, polyisocyanate, silane coupling agent, water removal agent and inorganic filler, combined with long branched structure organotin compound catalyst to ensure long operating time at room temperature and can Shorten the positioning time by heating.
It realizes polyurethane adhesive with operating time up to more than 60 minutes at room temperature. It significantly improves the curing speed through short-term heating and shortens the positioning time. It also has a high bonding strength to aluminum and PET after curing. It is suitable for large-scale and complex battery power. Core parts are bonded and fixed.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane adhesives, and in particular to a two-component polyurethane structural adhesive and application thereof. Background Art
[0002] In the design of power batteries, in order to reduce the weight of the battery pack and increase the energy density, the battery cells and the battery cells and the shell are bonded and fixed with two-component polyurethane structural adhesive. In the assembly process of large battery packs, there are many processes and it takes a long time, and after the assembly is completed, it needs to move to the next process immediately. In order to meet this process requirement, battery manufacturers have added short-term heating measures to promote the rapid curing and positioning of the adhesive. This process requires the adhesive to have a long operating time and can cure quickly under short-term heating conditions.
[0003] In the prior art, the operation time of polyurethane adhesive can be extended by selecting special catalysts, and the curing speed of polyurethane adhesive can be accelerated under special conditions, but there are limitations in its use due to the influence of the use conditions. For example, patent document CN102533200B discloses a two-component polyurethane adhesive, the raw material composition and weight percentage of component A are 0-10% monohydric alcohol, 30-90% polyol, 8-60% pigment filler, 1-10% nanofiller, 0.01-1% catalyst, 0.1-5% silane coupling agent; component B is isocyanate. This patented technology specially encapsulates the catalyst in a hydroxyl resin, and during use, the catalyst is released by the simultaneous action of water and isocyanate to achieve the effect of rapid catalytic curing. However, moisture will cause polyurethane to solidify and foam, affecting adhesion. Moreover, moisture will affect the insulation performance of electronic components, especially battery cells. This patented technology is not suitable for the electronic component industry that strictly eliminates moisture. Patent document CN104164206A discloses a method for preparing a heat-sensitive polyurethane potting adhesive, and the preparation steps are: polyether polyol, dibutyltin dilaurate, 1,2-dimethylimidazole or N,N',N"-trimethylaminoethylpiperazine, and bis(dimethylaminoethyl)ether derivatives are mixed evenly as a polyol component. The flame retardant and the polyisocyanate are mixed evenly to obtain a polyisocyanate component. The polyol component and the polyisocyanate component are mixed evenly in a mass ratio of 100:50 to 100, and degassing is performed to obtain a heat-sensitive polyurethane potting adhesive. The polyurethane potting adhesive prepared by this method has a long operation time, and the curing speed can be adjusted by temperature. However, the used heat-sensitive catalyst and heat-sensitive auxiliary agent are both amines, and there is a problem of curing and foaming under the interference of moisture, which limits the use of the potting adhesive. In addition, the polyurethane potting adhesive has low strength and is not suitable for structural bonding.
[0004] To this end, it is necessary to develop a two-component polyurethane structural adhesive with a long operating time and the ability to shorten the positioning time by heating, which can be used for the bonding and fixation of large-scale battery cell components with complex processes. Summary of the invention
[0005] Based on this, it is necessary to provide a two-component polyurethane structural adhesive and its application, which can have a long operating time and can shorten the positioning time by heating.
[0006] The present invention adopts the following technical solution:
[0007] The present invention provides a heat-conductive two-component polyurethane structural adhesive, comprising component A and component B;
[0008] The component A is mainly prepared from the following raw materials in parts by weight: 150-200 parts of bisphenol A modified polyether polyol, 220-300 parts of castor oil modified polyol, 100-150 parts of dimer acid modified polyester polyol, 10-20 parts of chain extender, 3-5 parts of first catalyst, 300-450 parts of first filler, 10-30 parts of first thixotropic agent, 1-3 parts of pigment and 20-30 parts of first dewatering agent;
[0009] The B component is mainly prepared from the following raw materials in parts by weight: 600-650 parts of terminal isocyanate polyurethane prepolymer, 40-50 parts of polyisocyanate, 5-7 parts of silane coupling agent, 20-30 parts of second water scavenger, 250-320 parts of second filler and 10-30 parts of second thixotropic agent; and the terminal isocyanate polyurethane prepolymer is prepared by reacting dimer acid-modified polyester polyol, polyisocyanate, plasticizer and second catalyst in a weight ratio of (240-540):(430-720):(30-50):(0.02-0.05);
[0010] Wherein, the first catalyst is an organic tin compound with a long branched chain structure, and the general structural formula is as follows:
[0011]
[0012] Wherein m, n are integers greater than 3 and less than 9; a, b, c, d are integers greater than 0 and less than 7; R 1 and R 3 for or -CH 2 -; R 2 and R 4 H, -CH 3 or -CH 2 -CH 3 .
[0013] The first catalyst is preferably one of DABCO T131 of Air Products, KOSMOS T820 and KOSMOS 16 of Evonik.
[0014] In some embodiments, the bisphenol A modified polyether diol has a relative molecular weight of 350-500 and a hydroxyl value of 220-295 mgKOH / g. Preferably, the bisphenol A modified polyether diol is Arkema 330HP from France, BAP-3 from China Taiwan Synthetic Chemical Co., Ltd., and Koremul-BSA-40, Koremul-BSA-60, and Koremul-BSA-30F from Hannong, South Korea.
[0015] In some embodiments, the castor oil modified polyol is selected from at least one of ALBODUR 955, ALBODUR 956, ALBODUR 965 of Germany's Opel and AC-009 of Japan's Ito Oil.
[0016] In some of the embodiments, the dimer acid-modified polyester polyol has a relative molecular weight of 1800-2100 and a hydroxyl value of 52-60 mgKOH / g, preferably DA21 and DA2110 from Shanghai Jingri and Radia 7287 from Oleon of Belgium.
[0017] In some of the embodiments, the chain extender is a diol containing a primary hydroxyl group, with a relative molecular weight of 50 to 150, preferably at least one of dipropylene glycol, diethylene glycol, 1,4-butanediol, and ethylene glycol.
[0018] In some embodiments, the first filler and the second filler are both selected from at least one of aluminum hydroxide, aluminum oxide, hollow glass microspheres, and stearic acid-modified ultrafine calcium carbonate, with a particle size of 5-40 μm and a surface treated with an alkoxysilane coupling agent.
[0019] In some embodiments, the pigment is preferably selected from iron black, phthalocyanine blue, and iron yellow.
[0020] In some embodiments, the first thixotropic agent and the second thixotropic agent are both hydrophobic fumed silica, preferably Degussa R972 from the United States.
[0021] In some embodiments, the first water scavenger and the second water scavenger are preferably selected from 4A molecular sieves.
[0022] In some embodiments, the polyisocyanate is selected from at least one of 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate (HDI) trimer, preferably at least one of H12MDI, IPDI from Yantai Wanhua, and desmodur N3300 from Bayer.
[0023] In some embodiments, the silane coupling agent is selected from at least one of β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.
[0024] In some embodiments, the plasticizer is selected from at least one of isopropylated triphenyl phosphate, tricresyl phosphate, tolyl diphenyl phosphate, and diphenyl isooctyl phosphate.
[0025] In some embodiments, the second catalyst is at least one of dibutyltin dilaurate, stannous octoate, and bismuth neodecanoate.
[0026] The present invention provides a method for preparing a two-component polyurethane structural adhesive, comprising the following steps:
[0027] Preparation of component A: weighing the raw materials according to the composition of component A of the thermally conductive two-component polyurethane adhesive described in any one of the above, evacuating, stirring and dispersing evenly, and obtaining the component A;
[0028] Preparation of component B:
[0029] Preparation of isocyanate-terminated polyurethane prepolymer: according to the composition of the isocyanate-terminated polyurethane prepolymer described in any one of the above, add polyester polyol and plasticizer into a flask, heat to 115°C-120°C, evacuate, stir to dehydrate, cool to 60°C, release the vacuum with nitrogen, add polyisocyanate and second catalyst, heat to 80°C, keep warm for reaction for 1.5-2h, cool to 60°C while stirring, and seal for storage;
[0030] According to the composition of component B of the thermally conductive two-component polyurethane adhesive described in any one of the above items, various raw materials are weighed, vacuumed, stirred and dispersed evenly to obtain the adhesive.
[0031] The present invention also provides the use of the above two-component polyurethane structural adhesive in the preparation of large-scale battery core components with complex processes.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The two-component polyurethane adhesive of the present invention is prepared by screening bisphenol A modified polyether polyol, castor oil modified polyol, heat activated catalyst, inorganic filler, thixotropic agent and dewatering agent of specific types and proportions to prepare component A, and by preparing component B by specific types and proportions of isocyanate-terminated polyurethane prepolymer, polyisocyanate, silane coupling agent, dewatering agent, inorganic filler and thixotropic agent. When component A and component B are compounded in a volume ratio of 1:1, the operating time at room temperature can reach more than 60 minutes, the curing speed can be increased by short-term heating, the positioning time can be shortened, the bonding strength to aluminum and PET is high after curing, and the adhesive is suitable for bonding and fixing of large battery cell components with complex processes. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.
[0035] The following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.
[0036] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.
[0037] Sources of some materials and description of physical and chemical parameters:
[0038] Bisphenol A modified polyether diols were purchased from: Arkema 330HP (relative molecular weight 400, hydroxyl value 280 mgKOH / g) from France, BAP-3 (relative molecular weight 395, hydroxyl value 285 mgKOH / g) from China Taiwan Sino-Japan Synthetic Chemical Co., Ltd., and Koremul-BSA-40 (relative molecular weight 410, hydroxyl value 278 mgKOH / g), Koremul-BSA-60 (relative molecular weight 500, hydroxyl value 225 mgKOH / g) and Koremul-BSA-30F (relative molecular weight 400, hydroxyl value 280 mgKOH / g) from Korea Hannong.
[0039] Castor oil modified polyols were purchased from: ALBODUR 955 (relative molecular weight 387, hydroxyl value 290 mgKOH / g), ALBODUR 956 (relative molecular weight 368, hydroxyl value 305 mgKOH / g), ALBODUR 965 (relative molecular weight 385, hydroxyl value 291 mgKOH / g) from Germany's Opel Co., Ltd. and AC-009 (relative molecular weight 500, hydroxyl value 223 mgKOH / g) from Ito Oil Co., Ltd. of Japan.
[0040] The dimer acid-modified polyester polyols were purchased from: DA21 (relative molecular weight 2000, hydroxyl value 56 mgKOH / g), DA2110 (relative molecular weight 2000, hydroxyl value 56 mgKOH / g) from Shanghai Jingri, and Radia 7287 (relative molecular weight 2000, hydroxyl value 56 mgKOH / g) from Oleon, Belgium.
[0041] Organic tin compounds with long branched chain structures: DABCO T131 from Air Products and Chemicals, KOSMOS T820 and KOSMOS16 from Evonik.
[0042] Polyisocyanate: H12MDI and IPDI from Yantai Wanhua, and desmodur N3300 from Bayer.
[0043] Example 1
[0044] This embodiment provides a two-component polyurethane structural adhesive, the composition of which is shown in Table 1 below:
[0045] Table 1 Composition of the two-component polyurethane structural adhesive of Example 1
[0046]
[0047]
[0048] The preparation method of the two-component polyurethane structural adhesive of this embodiment comprises the following steps:
[0049] Preparation of component A: weigh the raw materials according to the composition in Table 1, evacuate the mixture, stir and disperse evenly to obtain component A1.
[0050] Preparation of component B:
[0051] Preparation of terminal isocyanate prepolymer 1: According to the amounts in Table 1, Radia 7287 and isopropylated triphenyl phosphate were added to a flask, the temperature was raised to 120°C, the flask was evacuated to -0.095 MPa, and the mixture was stirred for dehydration for 2 h. The temperature was then lowered to 60°C, the vacuum was released with nitrogen, H12MDI and stannous octoate were added, the temperature was raised to 80°C, the reaction was kept at this temperature for 2 h, the temperature was lowered to 60°C while stirring, and the mixture was sealed for storage.
[0052] Then weigh the raw materials according to the composition in Table 1, evacuate, stir and disperse evenly to obtain component B1.
[0053] Put A1 and B1 into 1:1 plastic double tube packaging, seal and store, and use together.
[0054] Example 2
[0055] This embodiment provides a two-component polyurethane structural adhesive, the composition of which is shown in Table 2 below:
[0056] Table 2 Composition of the two-component polyurethane structural adhesive of Example 2
[0057]
[0058] The preparation method of a two-component polyurethane structural adhesive of this embodiment comprises the following steps:
[0059] Preparation of component A: Weigh the raw materials according to the composition in Table 2, evacuate the mixture, stir and disperse evenly to obtain component A2.
[0060] Preparation of component B:
[0061] Preparation of terminal isocyanate prepolymer 2: According to the proportion in Table 2, DA21 and tricresyl phosphate were added to a flask, the temperature was raised to 120°C, the mixture was evacuated to -0.095 MPa, and the mixture was stirred for dehydration for 2 h. The temperature was then lowered to 60°C, the vacuum was released with nitrogen, IPDI and dibutyltin dilaurate were added, the temperature was raised to 80°C, the mixture was kept for reaction for 2 h, the temperature was lowered to 60°C while stirring, and the mixture was sealed for storage.
[0062] Weigh each raw material according to the composition in Table 2, evacuate, stir and disperse evenly to obtain component B2.
[0063] Put A2 and B2 into 1:1 plastic double tube packaging, seal and store, and use together.
[0064] Example 3
[0065] This embodiment provides a two-component polyurethane structural adhesive, the composition of which is shown in Table 3 below:
[0066] Table 3 Composition of the two-component polyurethane structural adhesive of Example 3
[0067]
[0068]
[0069] The preparation method of a two-component polyurethane structural adhesive of this embodiment comprises the following steps:
[0070] Preparation of component A: weigh the raw materials according to the composition in Table 3, evacuate the mixture, stir and disperse evenly to obtain A3.
[0071] Preparation of component B:
[0072] Preparation of terminal isocyanate prepolymer 3: According to the ratio in Table 3, DA2110 and toluene diphenyl phosphate were added to a flask, the temperature was raised to 120°C, the mixture was evacuated to -0.095 MPa, and the mixture was stirred for dehydration for 2 h. The temperature was then lowered to 60°C, the vacuum was released with nitrogen, desmodur N3300 and bismuth neodecanoate were added, the temperature was raised to 80°C, the reaction was kept at this temperature for 2 h, the temperature was lowered to 60°C while stirring, and the mixture was sealed and stored for later use.
[0073] Weigh the raw materials according to the composition in Table 3, evacuate the mixture, stir and disperse evenly to obtain B3.
[0074] Put A3 and B3 into 1:1 plastic double tube packaging, seal it and use it together.
[0075] Example 4
[0076] This embodiment provides a two-component polyurethane structural adhesive, the composition of which is shown in Table 4 below:
[0077] Table 4 Composition of the two-component polyurethane structural adhesive of Example 4
[0078]
[0079]
[0080] The preparation method of a two-component polyurethane structural adhesive of this embodiment comprises the following steps:
[0081] Preparation of component A: weigh the raw materials according to the composition in Table 3, evacuate the mixture, stir and disperse evenly to obtain A4.
[0082] Preparation of component B:
[0083] Preparation of terminal isocyanate prepolymer 4: According to the proportion in Table 4, DA21 and diphenyl isooctyl phosphate were added to a flask, the temperature was raised to 120°C, the mixture was evacuated to -0.095 MPa, and the mixture was stirred for dehydration for 2 h. The temperature was then lowered to 60°C, the vacuum was released with nitrogen, IPDI and dibutyltin dilaurate were added, the temperature was raised to 80°C, the mixture was kept warm for 2 h, the temperature was lowered to 60°C while stirring, and the mixture was sealed for storage.
[0084] Weigh the raw materials according to the composition in Table 4, evacuate the mixture, and stir to disperse the mixture evenly to obtain B4.
[0085] Put A4 and B4 into 1:1 plastic double tube packaging, seal and store, and use together.
[0086] Comparative Example 1
[0087] This comparative example provides a two-component polyurethane structural adhesive. The material ratio and preparation process are the same as those in Example 1, except that the long-chain branched organic tin compound catalyst of component A is replaced by dibutyltin dilaurate in equal amounts. The other material types and proportions remain unchanged.
[0088] Comparative Example 2
[0089] This comparative example provides a two-component polyurethane structural adhesive. The preparation process is the same as that of Example 1, except that the long-chain branched organic tin compound catalyst of component A is replaced with dibutyltin dilaurate, and its addition amount is reduced to 1 part. Other material types and proportions remain unchanged.
[0090] Comparative Example 3
[0091] This comparative example provides a two-component polyurethane structural adhesive. The preparation process is the same as that of Example 1, except that component A does not contain dipropylene glycol chain extender, and the types and proportions of other materials remain unchanged.
[0092] Comparative Example 4
[0093] This comparative example provides a two-component polyurethane structural adhesive. The preparation process is the same as that of Example 1, and the only difference is that in the preparation raw materials of the terminal isocyanate prepolymer and component B, H12MDI is replaced with diphenylmethane diisocyanate MDI-100 of Yantai Wanhua, and other material types and proportions remain unchanged.
[0094] Comparative Example 5
[0095] This comparative example provides a two-component polyurethane structural adhesive. The preparation process is the same as that of comparative example 4, except that the amount of catalyst DABCO T131 in component A is reduced to 0.1 parts, and the types and proportions of other materials remain unchanged.
[0096] Performance Testing
[0097] The polyurethane structural adhesives prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were respectively subjected to performance tests:
[0098] (1) Operation time test: In an environment with a temperature of (23±2)℃ and a relative humidity of (50±5)%RH, mix about 20g of components A and B in a volume ratio of 1:1 and start timing. At regular intervals, touch the surface of the colloid with a glass rod and record the time when the surface of the colloid does not draw.
[0099] (2) Short-term strength test by heating and curing: The test was conducted in accordance with GB / T 7124-2008. Components A and B were mixed evenly in a volume ratio of 1:1. 3003 aluminum materials without primer coating and surface treatment were bonded to 3003 aluminum materials to prepare shear test pieces. The shear test pieces were placed in an oven at 80°C and cured for 5 min, 7 min, 9 min, 11 min, 13 min, 15 min, and 17 min, respectively. The shear strength was then tested immediately at room temperature after being taken out.
[0100] (3) Room temperature fully cured shear strength test: The test was conducted in accordance with GB / T 7124-2008. Components A and B were mixed evenly in a volume ratio of 1:1. PET blue film without primer coating and surface treatment was bonded to 3003 aluminum, and 3003 aluminum was bonded to 3003 aluminum to prepare shear test pieces. The shear test pieces were cured at a temperature of (23±2)°C and a relative humidity of (50±5)%RH for 7 days, and the shear strength was tested.
[0101] (4) Tensile strength and elongation at break test: Components A and B were mixed evenly in a volume ratio of 1:1 and pressed into a sheet with a thickness of about 2 mm. The sheets were cured for 7 days at a temperature of (23 ± 2) °C and a relative humidity of (50 ± 5) % RH. The test was performed according to the standard using a Type I tool.
[0102] The corresponding test results are shown in Table 5 below:
[0103] Table 5 Performance test results statistics
[0104]
[0105]
[0106] It can be seen from the above table that the two-component polyurethane structural adhesive prepared in Examples 1-4 has an operation time of more than 60 min, and its heating and curing strength increases rapidly. The shear strength after heating and curing at 80°C for 15 min reaches more than 0.6 MPa, and the shear strength after complete curing at room temperature is greater than 10 MPa, the tensile strength is greater than 9 MPa, and the elongation at break is greater than 50%. It is suitable for bonding and fixing of large-scale battery cell components with complex processes.
[0107] However, the increase in heat-curing strength in Comparative Example 1 is not as great as that in Example 1, and the operation time is very short. The operation time of Comparative Example 2 is extended, but the increase in heat-curing strength is smaller. It can be seen from Comparative Examples 1 and 2 that conventional organotin catalysts can only accelerate the heat curing speed by increasing the usage, but the operation time is also shortened, and it is difficult to take into account both long operation time and rapid heat curing. The operation time of Comparative Example 3 is longer, but the increase in heat curing strength is smaller than that of Example 1, indicating that the use of a specific type of chain extender helps to improve the heat curing speed of the two-component polyurethane structural adhesive of the present invention. The increase in heat curing strength of Comparative Example 4 is relatively large, but the operation time is very short. The operation time of Comparative Example 5 is longer, but the increase in heat curing strength is significantly smaller than that of Comparative Example 4, indicating that the use of a specific type of isocyanate is difficult to take into account both long operation time and rapid heat curing.
[0108] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A two-component polyurethane structural adhesive, characterized in that: It includes component A and component B which are mixed in a volume ratio of 1:1 during application; The component A is mainly prepared from the following raw materials in parts by weight: 150-200 parts of bisphenol A modified polyether polyol, 220-300 parts of castor oil modified polyol, 100-150 parts of dimer acid modified polyester polyol, 10-20 parts of chain extender, 3-5 parts of first catalyst, 300-450 parts of first filler, 10-30 parts of first thixotropic agent, 1-3 parts of pigment and 20-30 parts of first dewatering agent; The B component is mainly prepared from the following raw materials in parts by weight: 600-650 parts of terminal isocyanate polyurethane prepolymer, 40-50 parts of polyisocyanate, 5-7 parts of silane coupling agent, 20-30 parts of second water scavenger, 250-320 parts of second filler and 10-30 parts of second thixotropic agent; and the terminal isocyanate polyurethane prepolymer is prepared by reacting dimer acid-modified polyester polyol, polyisocyanate, plasticizer and second catalyst in a weight ratio of (240-540):(430-720):(30-50):(0.02-0.05); Wherein, the first catalyst is an organic tin compound with a long branched chain structure, and the general structural formula is as follows: wherein m and n are integers greater than 3 and less than 9; a, b, c, d are integers greater than 0 and less than 7; R1 and R3 are selected from or -CH2-; R2 and R4 are H, methyl or ethyl; The first catalyst is selected from at least one of DABCOT131, KOSMOST820, and KOSMOS16; The chain extender is a diol containing primary hydroxyl groups, and the relative molecular weight is 50 to 150; The polyisocyanate is selected from at least one of 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate (HDI) trimer; The second catalyst is at least one of dibutyltin dilaurate, stannous octoate, and bismuth neodecanoate.
2. The two-component polyurethane structural adhesive according to claim 1, characterized in that: The relative molecular weight of the bisphenol A modified polyether polyol is 350-500, and the hydroxyl value is 220-295 mgKOH / g; and / or The relative molecular weight of the castor oil modified polyol is 360-550, and the hydroxyl value is 190-310 mgKOH / g; and / or The dimer acid-modified polyester polyol has a relative molecular weight of 1800-2100 and a hydroxyl value of 52-60 mgKOH / g.
3. The two-component polyurethane structural adhesive according to claim 1, characterized in that: The first filler and the second filler are both selected from at least one of aluminum hydroxide, aluminum oxide, hollow glass microspheres and stearic acid-modified ultrafine calcium carbonate, with a particle size of 5-40 μm and a surface treated with an alkoxysilane coupling agent.
4. The two-component polyurethane structural adhesive according to claim 1, characterized in that: The first thixotropic agent and the second thixotropic agent are both hydrophobic fumed silica; and / or The pigment is one of iron black, phthalocyanine blue and iron yellow; and / or The first dehydrating agent and the second dehydrating agent are both 4A molecular sieves.
5. The two-component polyurethane structural adhesive according to claim 1, characterized in that: The silane coupling agent is selected from at least one of β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane; and / or The plasticizer is selected from at least one of isopropylated triphenyl phosphate, tricresyl phosphate, tolyl diphenyl phosphate and isooctyl diphenyl phosphate.
6. Use of the two-component polyurethane structural adhesive according to any one of claims 1 to 5 in the preparation of battery core components.
Citation Information
Patent Citations
Bi-component polyurethane adhesive
CN102533200B
Preparation method of thermosensitive polyurethane embedding adhesive
CN104164206A
Two-component polyurethane adhesive and application thereof
CN111808570A
Two-component polyurethane adhesive and preparation method thereof
CN113717677A
Heat-conducting two-component polyurethane adhesive and preparation method and application thereof
CN113999643A